Pemberdayaan Ekonomi Kelompok Usaha Bersama Untuk Meningkatkan Kesejahteraan Masyarakat (Studi Di Kube Waroh Dusun Penangka Desa Sesaot) - Laili Hurriati (Universitas Hamzanwadi, 2020)
This study aims to determine the effectiveness of economic empowerement through joint business group (kelompok usaha bersama), hereinafter referred to as KUBE, to improve community welfare in KUBE Waroh, Penangka sub-village of Sesaot Village. This study employs qualitative approach in order to examine how the economic empowerement could improve community welfare in KUBE Waroh, Penangka of Sesaot Village. The KUBE program involves activities which help the community to gain knowledge, skills and experience whereby the activities are delivered by the group established with common goals. By improving the quality of human resources, then, it is hoped that the beneficiaries’ access to work will increase too. The result of this study shows that the economic empowerment through the implementation of the KUBE program towards the KUBE Waroh members could bring positive impacts to the members. It is evident from the fact that now the members are becoming economically productive, participating in an economically productive activity, mirroring the increase in the members’ economic welfare.